1986
DOI: 10.1177/002248718603700208
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teachers' Salaries and Non-salary Benefits

Abstract: Rowsey and Ley asked undergraduate students in education and engineering to estimate the mean salaries for four groups: beginning teachers in Alabama, all teachers in Alabama, beginning teachers in the United States, and all teachers in the United States. Although estimates made by prospective engi neers were generally more accurate than were those made by prospective teachers, both samples underestimated mean salaries for all but one group, be ginning teachers in the United States. Males in both samples gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The failure of "Inadequate salary" to load on any factor, taken together with its high mean score, would seem to suggest that Barbadian teachers view this source of discontent as a serious but isolated grievance vis-a-vis other professional considerations. Nevertheless, Rowsey and Ley (1986) have recently suggested that the failure of school authorities to keep teachers happy in terms of salary, and the various "fringe benefits'' of teaching, such as long holidays, may act to seriously undermine teachers' ability to derive satisfaction from other aspects of their work. This may be extremely pertinent to further evaluation of the situation in Barbados, since the responses of our teachers suggest that (with the exception of salary) highest levels of reported stress derive essentially from failure to experience satisfaction from intrinsic aspects of their job.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of "Inadequate salary" to load on any factor, taken together with its high mean score, would seem to suggest that Barbadian teachers view this source of discontent as a serious but isolated grievance vis-a-vis other professional considerations. Nevertheless, Rowsey and Ley (1986) have recently suggested that the failure of school authorities to keep teachers happy in terms of salary, and the various "fringe benefits'' of teaching, such as long holidays, may act to seriously undermine teachers' ability to derive satisfaction from other aspects of their work. This may be extremely pertinent to further evaluation of the situation in Barbados, since the responses of our teachers suggest that (with the exception of salary) highest levels of reported stress derive essentially from failure to experience satisfaction from intrinsic aspects of their job.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to improve teacher's professional skills and knowledge and make them happier and satisfied with their jobs thereby putting more effects to help achieve the goals of the educational institutions. In similar developments, Rowsey and Ley (2009) [44] identifies several factors as a major source of occupational stress among teachers in schools. Prominent among these factors are; poor working environment, delayed/nonpayment of salaries, delay in promotion, misbehavior of students, lack of resources for teaching, lack of in-service training and students poor attitude to learning.…”
Section: Introductionmentioning
confidence: 94%
“…C'est ainsi que si, dans quelques rares pays, les enseignants se disent satisfaits de leur salaire (Berthelot 1991;Gandara 1992), dans beaucoup d'autres, c'est l'insatisfaction qui prédomine. Ces résultats sont confirmés par diverses études : Wyllie (1966), Phipps (1968), Nelson (1970), Rowsey et Ley (1986), Raffel et Groff (1990), Campbell et Neill (1991), Valerio (1991), Chapman, Snyder et Burchfield (1993), Samoff (1994) et Imaz (1995. Sur le facteur ici étudié, Tiffin et Mc Cormick (1965) relèvent aussi que le salaire est rarement cité comme un des principaux éléments influençant la satisfaction ; par contre, le niveau de satisfaction diffère selon l'emploi occupé.…”
Section: Le Cadre Théoriqueunclassified